Good participatory practice : (UNAIDS, 2007)
These Good Participatory Practice guidelines aim to provide systematic guidance on the roles and responsibilities of entities funding and conducting biomedical HIV prevention trials towards participants and their communities. Such entities include investigators, research staff, pharmaceutical industry sponsors, foundations, government-supported research networks, non-governmental research sponsors, and all others involved in designing, financing, and executing clinical trials research.